Complete Genome Sequence of Lactobacillus plantarum Strain B21, a Bacteriocin-Producing Strain Isolated from Vietnamese Fermented Sausage Nem Chua - Golneshin, Aida (Genome Announc, 2015)
Lactobacillus plantarum strain B21 was isolated from Vietnamese sausage (nem chua) and demonstrated broad antimicrobial activity due to the production of bacteriocins. Here, we report the complete genome sequence of this strain (3,284,260 bp).